A CASE OF TRANSIENT DIABETES MELLITUS POST COVID-19 INDUCED DIABETES KETOACIDOSIS - Samingan, Nurshadia; Mavinkurve, Meenal; Yaakop, Siti Zarina; Jalaludin, Muhammad Yazid; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The recent COVID-19 pandemic has highlighted the intimate connection between this novel virus and numerous endocrinopathies. Several studies reported increased incidence of paediatric diabetes particularly Type 1 diabetes mellitus presenting with diabetes ketoacidosis (DKA). We report a case of transient diabetes mellitus that presented in DKA secondary to COVID-19 infection. CASE A 15-year-old male with underlying pineal gland germinoma previously treated with surgery and cranial irradiation presented with a COVID-19 infection. He was treated for panhypopituitarism with thyroxine, hydrocortisone and DDAVP. Low dose growth hormone (GH) (0.016 mg/kg/day) was started after 5-years clinical remission. Pre-GH, his BMI was 24.2kg/m2 and the HbA1c was 4.9%. He complained of fever, respiratory distress, lethargy and reduced oral intake. At presentation, the plasma glucose was 52.2 mmol/L with high serum ketones of 7.6 mmol/L. Blood gas was acidotic (pH 7.25, bicarbonate 14.2 mmol/L). The Hba1c was 12.5% and the C-peptide was low. His COVID-19 PCR was positive. Fluid bolus was delivered, and he was managed as per DKA protocol. Stress dose hydrocortisone was given. After 12 hours he was transitioned to basal bolus subcutaneous insulin. After 1 month, he had recurrent hypoglycaemia prompting a reduction in the insulin doses and discontinuation after 2 months. The HbA1c and C-peptide level without insulin were 6.2% and 2.9 mg/ml respectively. His diabetes autoantibodies were negative. CONCLUSION COVID-19 infection is a potential trigger for development of new onset diabetes mellitus due to glucose dysregulation or autoantibody development. In our case, antibodies were negative and insulin dependency was temporary despite classically presenting with DKA. Long term follow up is required to monitor his glycaemic status.